PENGKAJIAN PROGRAM KURSUS BIDANG PARIWISATA - Melati Indri Hapsari (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2017)
The objectives of this research are to find out (1) the condition of the course institution and training in tourism sector, (2) the mechanism of leraning of tourism in the institution of the course and training, (3) the programs that can be developed in the field of tourism, (4) tourism profession, and (5) competency test mechanism in the certification body. The research was conducted at the Institution of Course and Training (ICT) in the field of toursm in Central Java and Yogyakarta as from August - September 2016. This quantitative descriptive research with survey approach collected primary quantitative and qualitative data using interview and observation techniques and secondary data obtained from literature and document study. The data were analyzed quantitatively and qualitatively. The research results show that almost all ICT in tourism field targeted in this research are good enough. However, the instructional programs and strategies to develop are still mostly applying local curriculum created by the Institution itself not based on Indonesian Qualification Framework and international standard.